Significance of its Markers in Early Diagnosis of Acute Kidney Damage in Myocardial Infarction (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2025)
The article examines the issues of early detection of acute kidney injury in the acute phase of myocardial infarction, and a comparative analysis of NGAL, KIM-1 and cystatin C indicators is carried out. ROC analysis showed that NGAL (AUC=0.84, p